PENGARUH PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) DENGAN MEDIA QUIZIZ TERHADAP MOTIVASI BELAJAR DAN HASIL BELAJAR KOGNITIF MATA PELAJARAN INFORMATIKA SISWA KELAS VII SMP NEGERI 7 MALANG - Hermansyah; Irianto, Wahyu Sakti Gunawan; Wardhana, Nyoman Dedi Kusuma; Al-Jabbar, Habib Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This classroom action research aimed to examine the effectiveness of implementing the Team Game Tournament (TGT) cooperative learning model integrated with the Quizizz game-based platform in enhancing students’ learning motivation and achievement. The research subjects consisted of 24 students from Class VII H at SMP Negeri 7 Malang. One of the key elements in the implementation of the TGT model is the reward system, which is believed to increase students' interest and motivation to positively engage in competition. With the support of Quizizz as a learning medium, students were encouraged to develop a sense of responsibility in answering questions, both individually and collaboratively. This study employed a quantitative experimental approach using a pre-test and post-test control group design. The research was conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. Data collected included students’ learning activity and motivation. Learning activity was measured using an observation sheet on instructional implementation, assessed by a single observer. Meanwhile, learning motivation was measured using a questionnaire comprising 20 items, covering indicators such as attention, relevance, satisfaction, and confidence. The data were analyzed descriptively. The results of the study indicate that: 1.In Cycle I, students appeared less active and showed little initiative in taking notes on key points of the material. However, in Cycle II, students demonstrated increased engagement, actively responded to questions from the teacher and peers, and showed willingness to ask questions. 2. Students' learning motivation also improved: in Cycle I, 60% of students were categorized as highly motivated, 6.66% as moderately motivated, and 33% as poorly motivated. In Cycle II, 90% of students fell into the highly motivated category, while 10% were moderately motivated. These findings indicate that the application of the TGT learning model supported by the Quizizz platform is effective in enhancing students' classroom activity and learning motivation.